Productive and non-productive coping strategies of paralympian with different types of disorders - Shestilovskaya, Natalia A. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
Increasing of attention to the Paralympic movement and involvement of people with disabilities in professional sports makes actual studing the psychological characteristics of Paralympian, and in particular, the problem of overcoming stress especially for athlete with disabilities – the Paralympian. The article analyzes the differences between athletes with different disorders (with visual impairment, hearing impairment and wheelchair users.
Keywords: sport; adaptive sport; stress; coping strategies; Paralympian